2007
DOI: 10.1097/01.njh.0000299317.52880.ca
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Coping at the End of Life

Abstract: v Spiritual issues surface as people face death.Spiritual care is the core of care for the dying. Nurses are mandated to provide spiritual care, yet little is known about the impact of spirituality on the ability to cope at the end of life. The purpose of this correlational study was to examine relationships between spirituality and coping at end of life. Adults (n = 60) enrolled in hospice between ages 30 and 90 completed the Functional Assessment of Chronic Illness Therapy Spiritual Well-being Scale, the Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Among the 16 studies that examined the Meaning/Peace as one factor and its association with QOL, a positive association was evident in all except for one study. 41 This positive association was consistent for overall QOL (ranges from 0.49 to 0.70) and for physical (ranges from 0.25 to 0.28) and mental health (ranges from 0.55 to 0.73). 10,20,24,26 The correlation between Meaning/ Peace and mental health was found to be stronger than physical health in three studies, 11,29,45 although not for 288 BAI AND LAZENBY 2.…”
Section: Sample and Ethodological Characteristicssupporting
confidence: 57%
See 1 more Smart Citation
“…Among the 16 studies that examined the Meaning/Peace as one factor and its association with QOL, a positive association was evident in all except for one study. 41 This positive association was consistent for overall QOL (ranges from 0.49 to 0.70) and for physical (ranges from 0.25 to 0.28) and mental health (ranges from 0.55 to 0.73). 10,20,24,26 The correlation between Meaning/ Peace and mental health was found to be stronger than physical health in three studies, 11,29,45 although not for 288 BAI AND LAZENBY 2.…”
Section: Sample and Ethodological Characteristicssupporting
confidence: 57%
“…40 QOL outcomes were reported as overall QOL (total score or one-item global measure), summated scores of physical health (physical component summary [PCS]) or mental health (mental component summary [MCS]), or were broken down to domains of physical, social, emotional, and functional wellbeing. Four studies targeted the mental 27,35 or physical dimensions of QOL 17,41 without assessing overall QOL.…”
Section: Sample and Ethodological Characteristicsmentioning
confidence: 99%
“…One study examining the relationship between spiritual well-being and coping at endof-life explored the role of spiritual well-being in decision-making for patients in a hospice setting [37]. Sixty elder adults (mean age of 63) enrolled in hospice care completed the FACIT-Sp as well as the Serenity Scale and the Cognitive Coping Scale.…”
Section: Spiritual Well-being At the End-of-lifementioning
confidence: 99%
“…Nearly 70% are church members, and more than 40% have attended church, synagogue, or temple within the past 7 days (Koenig, 2002). In a study by Kruse et al (2007), highly significant positive correlations were found between spiritual well-being, peacefulness, comfort, and serenity for participants who were at the end of life. In this study, 73% of the participants reported that illness had strengthened their spiritual life and increased their religious practices.…”
Section: Spirituality Religion and Healthmentioning
confidence: 98%
“…In this study, 73% of the participants reported that illness had strengthened their spiritual life and increased their religious practices. These religious practices included praying, reading the Bible, attending church or mass, having visits from the chaplain, and receiving support from the church community (Kruse et al, 2007).…”
Section: Spirituality Religion and Healthmentioning
confidence: 99%